2022
DOI: 10.1371/journal.pone.0265913
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to high school and university students’ physical activity: A systematic review

Abstract: Physical inactivity commonly occurs throughout one’s life, particularly during adolescence and young adulthood. Multiple factors can negatively influence participation in physical activity, but there has been no review examining the barriers to physical activity among high school and university students. Therefore, the aim of this systematic review was to summarize evidence of barriers to the practice of physical activity among high school and university students. The literature search was conducted without ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
28
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 155 publications
6
28
0
2
Order By: Relevance
“…Current life situation, financial situation, and other barriers, are leading barriers among the medical students in our research after faculty obligations. Similar to our study, Ferreira-Silva et al [ 63 ] emphasize that personal circumstances are also barriers to regular PA. The same study shows that the barriers to regular PA in the psychological, emotional, and cognitive categories are similar in students from all parts of the world.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Current life situation, financial situation, and other barriers, are leading barriers among the medical students in our research after faculty obligations. Similar to our study, Ferreira-Silva et al [ 63 ] emphasize that personal circumstances are also barriers to regular PA. The same study shows that the barriers to regular PA in the psychological, emotional, and cognitive categories are similar in students from all parts of the world.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, a significant amount of evidence has also demonstrated that, among university students, the lack of time, due to faculty obligations is the most common barrier to PA [ 19 , 37 , 62 ]. In a recent systematic review of various barriers to university students’ PA, 22 studies with university students were included [ 63 ]. The authors have also concluded that a lack of time, due to faculty obligations, was the most cited barrier to PA, among university students [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…В последние годы на фоне интенсификации учебного процесса в высших учебных заведениях наблюдается тенденция к снижению объема двигательной активности студентов, что негативно сказывается на показателях их физического развития. Одна из причин низкой физической активности -отсутствие мотивации, что согласуется с данными исследования [27].…”
Section: таблицаunclassified
“…Moreover, university students are also victim of low physical activity (PA) as previously reported in numerous studies (Ferreira et al, 2022;Garn and Simonton, 2022). This is because students spend more time in leisure activities, studying and preparing for their exams.…”
Section: Introductionmentioning
confidence: 97%